ANALISIS KEERATAN HUBUNGAN DI ANTARA PELANGGAN – KARYAWAN DAN PERUSAHAAN MENGGUNAKAN METODE HUMAN SIGMA (Studi Kasus : Jeng Dewi Wedding Organizer) - Sunaryo Sunaryo; Abdul Kholid (Teknoin, 2016)
One of the service  industry in Indonesia is wedding Organizer. It’s operation  is fasilitation in wedding fiesta. To increase the volume of operation, the Jeng Dewi Wedding Organizer has to createsquality of services. It can be done by increasing engagements and relations amongs employeecustomer and the company. Engagement amongs of them  will be the main factor  of the company’s sucsess. The customers has to be made satisfied by services. They are not satisfied by rational but olso by emotional. The customers which satisfied by services will results  a big profit. To do it coompany has to create a big engagements among of them. It needs an analysis, which can use  Human Sigma to measure the value of engagement. Human Sigma is a tool to analyse   the person’s emotinal . The result of this analysis is 35.5% for the value Human Sigma, 49 % for the value of Customers Engagement and 49 % for the value of  Employee Engagement. So the corporation  has to increase  all of this parameter.